Écriture créative, enjeux identitaires et plurilingues en langue seconde : une réflexion exploratoire, conceptuelle et empirique - Tracy BLOOR (E-REA)
This article is a theoretical and empirical exploration of innovative and experimental writing practices (Bing; Greaves and Di Stefano; Roche et al.; Bloor and Greaves; Robet & Mathis) in a second or foreign language (Dompmartin-Normand and Le Groignec; Mathis; Bloor and Greaves). It is based on an analysis of the author’s written expression in her second language, French. The article is composed of several parts. It begins with a clarification of several theoretical questions: what is a language? What is the role of identity in written expression in a second language? What are the objectives of creative writing in a second language in terms of progress in the language? To explore these questions, the paper first outlines the theoretical and methodological references—inspired by work in the field of comparative didactics—which underpin the study. Next, several short texts produced by the author during creative writing workshops are presented. The texts are then analyzed with the objective of identifying the kinds of issues of identity and plurilingualism that can be raised by participation in creative writing workshops.